2019
DOI: 10.1002/acr.23827
|View full text |Cite
|
Sign up to set email alerts
|

“Reluctant to Assess Pain”: A Qualitative Study of Health Care Professionals’ Beliefs About the Role of Pain in Juvenile Idiopathic Arthritis

Abstract: ObjectiveReducing pain is one of the main health priorities for children and young people with juvenile idiopathic arthritis (JIA); however, some studies indicate that pain is not routinely assessed in this patient group. The aim of this study was to explore health care professionals’ (HCPs) beliefs about the role of pain and the prioritization of its assessment in children and young people with JIA.MethodsSemi‐structured interviews were conducted with HCPs who manage children and young people with JIA in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…However, health care professionals in pediatric rheumatology sometimes neglect to assess pain because of a lack of time and tools available to do so. In addition, professionals may not perceive pain as a priority for their patients because the focus of consultations may be on disease activity and function rather than pain [7,8]. Pain conversations are difficult to have with patients.…”
Section: Chronic Pain In Juvenile Idiopathic Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…However, health care professionals in pediatric rheumatology sometimes neglect to assess pain because of a lack of time and tools available to do so. In addition, professionals may not perceive pain as a priority for their patients because the focus of consultations may be on disease activity and function rather than pain [7,8]. Pain conversations are difficult to have with patients.…”
Section: Chronic Pain In Juvenile Idiopathic Arthritismentioning
confidence: 99%
“…Decisions regarding the frequency of pain assessment administration rarely appear to be evidence based. This is a particular concern for health care professionals managing children and young people with JIA because they fear that more intense, regular pain assessment may lead to over-reporting or overexaggeration of pain or pain-related problems [7]. This phenomenon is called measurement reactivity, which is defined as a change in the variable being measured, because of the nature of the measurement method [21,22].…”
Section: Frequency Of Administrationmentioning
confidence: 99%
“…But while there is greater awareness of the importance of managing the psychosocial aspects of pain, this is often not addressed adequately in clinical practice. Healthcare professionals continue to use a more biomedical approach to understanding and managing pain, especially in JIA where pain is perceived by some to be directly and proportionately related to disease activity (Lee, Rashid, Thomson, & Cordingley, 2020). This suggests further research is needed to support healthcare professionals in translating understanding from pain theory and young people's experiences into their current practice.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of pain in children with arthritis is a common challenge for clinicians. A recent qualitative study found that health care professionals report gaps in pain‐specific knowledge and skills to assess pain in children with arthritis . In the context of assessment, it is important to recognize pain as a multidimensional experience that is comprised of sensory, affective, and evaluative components .…”
Section: Introductionmentioning
confidence: 99%
“…A recent qualitative study found that health care professionals report gaps in pain‐specific knowledge and skills to assess pain in children with arthritis . In the context of assessment, it is important to recognize pain as a multidimensional experience that is comprised of sensory, affective, and evaluative components . The sensory dimension is related to quality (what pain feels like), intensity (how much pain hurts), location (spatial distribution of pain), and duration (how long pain lasts).…”
Section: Introductionmentioning
confidence: 99%